Influence of glenohumeral joint muscle insertion on moment arms using a finite element model. Issue 14 (8th July 2020) - Hoffmann, M.; Begon, M.; Lafon, Y.; Duprey, S.
Abstract: Accurate muscle geometry is essential to estimate moment arms in musculoskeletal models. Given the complex interactions between shoulder structures, we hypothesized that finite element (FE) modelling is suitable to obtain physiological muscle trajectory. A FE glenohumeral joint model was developed based on medical imaging. Moment arms were computed and compared to literature and MRI-based estimation. Our FE model produces moment arms consistent with the literature and with MRI data (max 17 mm differences). The inferior and superior fibres of a same muscle can have opposite action; predictions of moment arms are sensitive to muscle insertion (up to 20 mm variation).